Պատկերամարտական շարժման սկզբնավորումն ու վարդապետական արձագանքը․ Վրթանես Քերթող և Հովհան Մայրագոմեցի - Բաղումյան, Զաքարիա ծ․ վրդ․
The iconoclastic movement in Armenia is an interesting phenomenon, which precedes the Byzantine controversies in the 8th century. Two important testimonies have been preserved in the Armenian ecclesiastical literature about the iconoclastic groups and movements in Armenia and Aghvank’ in the 6th–7th centuries: Vrt῾anes K῾ert῾oł’s treatise “Against the Iconoclasts” and the letter written by Hovhan Mayragomec῾i to Bishop David, which is included in the “History of Aghvank” by Movses Dasxowranc῾i, 10th century historian. These two complementary documents outline the origins of the iconoclastic movements in Armenia and Aghvank’, the reasons for its emergence, the geographical span and name of the movement’s authors showing the religious and theological attitude of the Armenian Church regarding the issue. The treatise of Vrt῾anes is the earliest datable defense of images in any language. The author proves necessity and importance of the icons in the churches on the basis of biblical and patristic sources, provides insightful information about the iconography and frescos of the Armenian churches in general. He cites St. John Chrysostom, Bishop Severian of Gabala, Eusebius of Caesarea and St. Gregory the Illuminator, the patron saint of the Armenian nation. Vrt῾anes is the first author to use the story of Abgar’s icon of Christ in Edessa in defense of icon use. Analyzing and studying the Armenian sources of the first stage of the iconographic movement, we come to the following conclusion: the presence of images in the church doesn’t contradict to the Holy Scriptures and the teaching of Church Fathers. We have to remember that the worship of images in Christianity has nothing to do with the idolatry described in the Old Testament, because icons were also in the Holy of Holies and in the Temple of Solomon.
Keywords: Հայոց եկեղեցի